2019
DOI: 10.21865/ridep50.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Fiabilidad y Validez de la Batería TGMD-2 en Población Española

Abstract: ResumenEste estudió analizó la fiabilidad y la validez de una versión en castellano de la batería de evaluación del desarrollo motor TGMD-2. Un total de 84 niños cumplimentaron la batería en dos ocasiones, con un intervalo de dos semanas para computar su fiabilidad test-retest. Dos evaluadores valoraron independientemente los resultados y se analizó fiabilidad inter-evaluador. Se estudió la validez de constructo siguiendo las indicaciones del manual de la batería y se valoró la condición física de los particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
0
10
1
4
Order By: Relevance
“…Alpha coefficients were calculated in different groups or participants for locomotor skills score (n = 18), ball skills score (n = 18), overall score (n = 12) and GMQ (n = 3). Ten studies reported alpha coefficients between 0.7 and 0.9 for locomotor skills score (4 over 0.9 [ 17 , 36 , 50 , 51 ]), 11 for ball skills score (3 over 0.9 [ 36 , 50 , 51 ]), 4 for overall score (3 over 0.9 [ 17 , 50 , 51 ]) and 3 for GMQ (2 over 0.9 [ 21 , 36 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Alpha coefficients were calculated in different groups or participants for locomotor skills score (n = 18), ball skills score (n = 18), overall score (n = 12) and GMQ (n = 3). Ten studies reported alpha coefficients between 0.7 and 0.9 for locomotor skills score (4 over 0.9 [ 17 , 36 , 50 , 51 ]), 11 for ball skills score (3 over 0.9 [ 36 , 50 , 51 ]), 4 for overall score (3 over 0.9 [ 17 , 50 , 51 ]) and 3 for GMQ (2 over 0.9 [ 21 , 36 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies shown inter-rater reliability values lower than 0.75 (ICC) [ 48 ] or 0.7 (kappa) [ 33 ], the last one comparing expert with novice coders. Scores of each individual skill were reported in 6 studies with more than ≈90% of the inter-rater reliability values over 0.6, ≈30% over 0.9 (ICC calculated in all comparisons) [ 35 , 36 , 42 , 46 , 48 , 50 ] (Figs 2 and 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations